2018
DOI: 10.1093/jxb/ery217
|View full text |Cite
|
Sign up to set email alerts
|

Three cytosolic glutamine synthetase isoforms localized in different-order veins act together for N remobilization and seed filling in Arabidopsis

Abstract: Glutamine biosynthesis for N-remobilization and seed filling in Arabidopsis is mainly catalysed by the three major GS1 isoforms, GLN1;1, GLN1;2, and GLN1;3, which are localized in different-order veins in the leaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 42 publications
4
72
0
1
Order By: Relevance
“…Glutamine and asparagine, with two N atoms per molecule, are considered as the preferential forms for long-distance translocation in plants. Therefore, the GS/GOGAT pathway and ASN genes play important roles in N metabolism and the interconversions of amino acids (Moison et al, 2018). Finally, these amino acids are loaded into phloem and transported to sink tissues with the participation of amino acid permeases (Tegeder and Ward, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Glutamine and asparagine, with two N atoms per molecule, are considered as the preferential forms for long-distance translocation in plants. Therefore, the GS/GOGAT pathway and ASN genes play important roles in N metabolism and the interconversions of amino acids (Moison et al, 2018). Finally, these amino acids are loaded into phloem and transported to sink tissues with the participation of amino acid permeases (Tegeder and Ward, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, GS1 is encoded by five individual isogenes with distinct affinities for NH 4 + and glutamate and tissue localization as well as distinct physiological functions (Guan et al , 2016; Guan et al , 2015; Ishiyama et al , 2004b; Konishi et al , 2017; Lothier et al , 2011; Moison et al , 2018). Phylogenetically, the nucleotide and amino acid sequences of these isoforms do not cluster with GS1 sequences from cereals (Thomsen et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moison et al. () demonstrated that the function of GS1:1, GS1:2, and GS1:3 could compensate each other in Arabidopsis while the gene expression and activity of chloroplastic GS2 in the diatom Thalassiosira pseudonana was stimulated by the presence of nitrate in the medium, but not ammonium (Glibert et al. ).…”
mentioning
confidence: 99%
“…The GS family contains GSI, GSII, and GSIII groups based on the molecular size and the number of subunits (Ghoshroy et al 2010). The number, expression, and function of GSII isoenzymes were most widely studied in higher plants and microalgae (Glibert et al 2016, Moison et al 2018, N emeth et al 2018, Wang et al 2018a. It was known that GSII consists of cytosolic GS1 and chloroplastic GS2 isoenzymes (Diaz et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation